Selection for morphology, gaits and functional traits in Lusitano horses: II. Fixed effects, genetic trends and selection in retrospect - Vicente, António (2014)
Mixed model procedures were used to analyze morphology and gaits records collected in about 18,000 Lusitano horses from 900 studs, over a period of 43 years, and functional records collected since 1998, to carry-out a critical assessment of the fixed effects and selection practices followed in this breed. Fixed effects considered in the analysis of morphology (head/neck, shoulder/withers, chest/thorax, back/loin, croup, legs and overall impression), gaits and final score (computed by summing partial morphological and gaits scores) were stud, year, sex, inbreeding and age. Functional traits analyzed were the scores obtained in working equitation dressage (WEDT) and maneability (WEMT) trials and in classical dressage (CD), where fixed effects were event, level of competition, sex, inbreeding and age. Phenotypic trends were moderate over the period analyzed, with a slight increase in height at withers, and a decline in final score. Nevertheless, differences among years were mostly environmental. Males received lower scores for almost all morphological and gaits traits except croup, with a difference of about −1.7 points for final score relative to females. Sex differences were small for functional traits, with general advantage of males in WEMT and CD, and a disadvantage in WEDT. Considerable differences were detected among studs, especially in their environmental effects but also in mean estimated breeding value (EBV), for morphology, gaits and functionality. The environmental effect of competition level in CD resulted in a progressively lower scoring as the competition became more difficult, while for WEMT the pattern was opposite and differences were minor for WEDT. Inbreeding depression was observed for all morphological and gait traits, but the magnitude of its impact was very small for all traits analyzed, never exceeding −0.1% of the mean per 1% inbreeding. Still, for functional traits the effect of inbreeding was negligible. The EBV for morphology, gaits, WEMT and WEDT show considerable variability, indicating that selection can be effective. For CD, however, the distribution of EBV was narrower. The genetic trend was positive but moderate for all traits, and it was slightly higher for head and neck, overall impression, gaits and final score. As a percentage of the mean, these traits and working equitation trials showed the highest responses, which in the best cases did not exceed 0.2% of the mean per year. Genetic selection differentials and the corresponding selection intensities were very modest for all traits analyzed, with a slightly higher intensity in sires when compared to dams.